Microstructure and Mechanical Property Correlation Between Rotary Friction Welded Nitinol–Nitinol Joints - Rehman, Ateekh Ur; Babu, Nagumothu Kishore; Talari, Mahesh Kumar; Usmani, Yusuf Siraj; Al-Khalefah, Hisham (Frontiers in Materials, 2021)
In the present study, a rotary friction welding process was used to join Nitinol in a similar welding combination. Macro and microstructure characteristics of the weld zone were compared with adjacent zones as well as the base metal. Hardness and tensile property of the joints were evaluated, and results were discussed in relation to weld microstructure. The weld macrostructure revealed uniform flash around the circumference of the weld. The optical microstructure of friction welded sample revealed fine recrystallized grains at the weld interface due to heavy deformation followed by dynamic recrystallization. The phase transformation behavior of base metal and welded samples were studied by differential scanning calorimeter (DSC). The drift in phase transformation temperatures after rotary friction welding may be attributed to fine grain formation at the weld interface. Friction welded samples exhibited improved yield strength and hardness values when compared to base metal due to grain refinement at the weld interface.